2012
DOI: 10.1175/mwr-d-11-00175.1
|View full text |Cite
|
Sign up to set email alerts
|

Usability of Best Track Data in Climate Statistics in the Western North Pacific

Abstract: Tropical cyclone (TC) activity for the last three decades shows strong discrepancies, deduced from different best track datasets (BTD) for the western North Pacific (WNP). This study analyzes the reliability of BTDs in deriving climate statistics for the WNP. Therefore, TC lifetime, operational parameters [current intensity (CI) number], and tracks are compared (for TCs identified concurrently) in BTD provided by the Joint Typhoon Warning Center (JTWC), the Japan Meteorological Agency (JMA), and the China Mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 21 publications
3
46
0
Order By: Relevance
“…Since the routine aircraft reconnaissance of WNP TCs ended in 1987 (e.g., Barcikowska et al 2012), the JMA best-track dataset relies mainly on empirically derived information obtained from estimates of TC intensity using the Dvorak current intensity technique (e.g., Velden et al 2006) of cloud-pattern recognition applied to satellite imagery rather than in situ observations. Thus, there is some inherent uncertainty in the JMA best-track dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Since the routine aircraft reconnaissance of WNP TCs ended in 1987 (e.g., Barcikowska et al 2012), the JMA best-track dataset relies mainly on empirically derived information obtained from estimates of TC intensity using the Dvorak current intensity technique (e.g., Velden et al 2006) of cloud-pattern recognition applied to satellite imagery rather than in situ observations. Thus, there is some inherent uncertainty in the JMA best-track dataset.…”
Section: Methodsmentioning
confidence: 99%
“…This table was derived based on matching their best track data during the reconnaissance era with reanalyzed CI numbers. The Koba et al (1990Koba et al ( , 1991 Barcikowska et al 2012).…”
Section: Heterogeneities In Tropical Cyclone Maximum Windsmentioning
confidence: 99%
“…They found that many of these relationships changed with time, exacerbating the challenge of reconciling these datasets. Other studies have examined how the best track heterogeneities have affected the climatology and trend analysis of tropical cyclones in individual regions, particularly the North Atlantic (Landsea 2007;Mann et al 2007;Vecchi and Knutson 2008;Landsea et al 2010) and west Pacific (Kamahori et al 2006;Yu et al 2007;Nakazawa and Hoshino 2009;Song et al 2010;Ren et al 2011;Barcikowska et al 2012;Knapp et al 2013). Kossin et al (2007Kossin et al ( , 2013 examined temporal heterogeneities in the best track dataset by comparing data from a single agency in each region with reanalyses based on homogenized satellite data (Knapp et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We recognize that a portion of the disagreements arise from several factors beyond Dvorak (pattern) interpretation, including different wind-averaging periods, inconsistent mapping of CI numbers to wind speeds, and other perceived regional bias adjustments. But recent work (Barcikowska et al 2012;Nakazawa and Hoshino 2009) demonstrates that significant interagency intensity differences in operational Dvorak estimates drive disparate best-track data, even after accounting for these factors.…”
mentioning
confidence: 99%